Obstructive sleep apnea: Dental perspective from upright to supine - Rupsa N Rout; Sanat K Bhuyan; Arpita Priyadarshini; Damodhar Bhindhani; Mamata Singh; Satya Mohapatra (Wolters Kluwer Medknow Publications, 2021)
Aim: To evaluate diagnostic cephalometric parameters and their influence on skeletal and soft tissue components in obstructive sleep apnea (OSA). Materials and Methods: The study is a prospective case study of 40 diagnosed cases (as diagnosed by Type IV level study) of obstructive sleep apnea who were reported to the Department of Oral Medicine and Radiology with their age ranging from 28 to 75 years. Lateral cephalometric radiographs in upright and supine posture were taken, with teeth in centric relation, and the head aligned with Frankfort horizontal (FH) plane parallel to the floor. The focus-coronal plane distance was 5 feet, the film-coronal plane distance was 15 cm, and the magnification was 10%. Results: OSA patients experience an increase in values of sella nasion point A (SNA) and sella nasion point B (SNB) at the supine position with respect to the upright position and experience a decrease in values of nasion sella turcica odontoid process tangent (NSL-OPT) and nasion sella turcica- cervical vertebra tangent (NSL-CVT) at the supine position with respect to the upright position. The parameters of paramount importance in the pathogenesis of OSA are soft palate thickness, length, and tongue length. Conclusion: SNA, SNB and NSL-OPT, NSL-CVT are inversely related to each other and play a role in the consequence or pathogenesis of OSA. Tongue height is of the least significance in the pathogenesis of OSA. The cephalometric findings are of paramount importance to know the exact site of obstruction in the pathogenesis of OSA.